Estudo óptico e comissionamento da linha de luz Carcará-X do Sirius - Astolfo, João Pedro Imbriani (Universidade Federal de São Carlos, 2022)
This work describes the optical study of the SIRIUS CARCARÁ-X beamline carried out with the optics group at the National Synchrotron Light Laboratory (LNLS). The line, in the commissioning phase, will be used to diagnose the machine's emittance and uses magnifying crystals in its design. Wave and geometric optics simulations to determine the intensity distribution of the light beam in different positions of the line, as well as studies of the behavior and sensitivity of the beam as a function of rotations and translations of the optical elements were carried out to determine configuration parameters and mechanical design for the CARCARÁ-X magnifier crystals. Once the initial beam and mechanical assembly parameters were defined, different case studies of the positioning of the CARCARÁ-X crystals were carried out to compare flow, alignment tolerances and ease of assembly from an engineering point of view. With these comparisons it is possible to define the ideal configuration of the magnifier crystals as being 1 x20 magnification crystal for each beam axis, horizontal and vertical. The applicability of genetic algorithms in automatic alignment procedures for complex optical systems and future perspectives of the code developed in this work are discussed. The efficiency of this algorithm for aligning a simulated beamline is clear, achieving 98% agreement with the intensity distribution specified for the ideal beamline, with no misalignments introduced.
Optical study and commissioning of the Sirius Carcará-X light line
Keywords: Óptica de Raios-X; Síncrotron; Algoritmos genéticos; Otimização; X-ray optics; Synchrotron; Genetic algorithms; Optimization; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA GERAL::INSTRUMENTACAO ESPECIFICA DE USO GERAL EM FISICA